Planting Islands: Marshall Islanders Shaping Land, Power, and History. Issue 2 (3rd April 2019) - LaBriola, Monica C.
ABSTRACT: This paper reframes encounters between ri-aelōñ-kein (Marshall Islanders) and ri-pālle (outsiders) between the 16th and 19th centuries through a ri-aelōñ-kein cultural lens. It applies a deep ethnographic approach and frameworks of cross-cultural exchange and mutual possession to re-present ri-aelōñ-kein engagements across the beach as purposeful attempts to 'plant' ri-pālle on land and within genealogies. It argues that, in addition to violence, ri-aelōñ-kein used 'gifts' of land and other exchanges to 'plant' ri-pālle within their realms and, in turn, augment their social status. While deployed most often by irooj (chiefs), kajoor (commoner) men and women used similar tactics with some success. Throughout, ri-aelōñ-kein made history by deploying aspects of culture to advance local ambitions through engagements with ri-pālle .